Undetectable Production of the VIM-1 Carbapenemase in an Atlantibacter hermannii Clinical Isolate - Girlich, Delphine; Bonnin, Rémy A.; Proust, Alexis; Naas, Thierry; Dortet, Laurent (Frontiers in Microbiology, 2021)
The differential expression of VIM-1 in Atlantibacter hermannii WEB-2 and Enterobacter hormaechei subsp. hoffmannii WEB-1 clinical isolates from a rectal swab from an hospitalized patient in France was investigated. A. hermannii WEB-2 was resistant to all β-lactams except carbapenems. It produced ESBL SHV-12 but the Carba-NP test failed to detect any carbapenemase activity despite the production of VIM-1. Conversely, E. hormaechei WEB-1, previously recovered from the same patient, was positive for the detection of carbapenemase activity. The blaVIM-1 gene was located on a plasmid and embedded within class 1 integron. Both plasmids were of the same IncA incompatibility group, and conferred the same resistance pattern when electroporated in E. coli TOP10 or E. cloacae CIP7933. Quantitative RT-PCR experiments indicated a weaker replication of pWEB-2 in A. hermanni as compared to E. hormaechei. An isogenic mutant of A. hermannii WEB-2 selected after sequential passages with increased concentrations of imipenem possessed higher MICs for carbapenems and cephalosporins including cefiderocol, higher levels of the blaVIM-1 gene transcripts and detectable carbapenemase activity using the Carba-NP test. Assessment of read coverage demonstrated that, a duplication of the region surrounding blaVIM-1 gene occurred in the A. hermannii mutant with detectable carbapenemase activity. The lack of detection of the VIM-1 carbapenemase activity in A. hermannii WEB-2 isolate was likely due to a weak replication of the IncA plasmid harboring the blaVIM-1 gene. Imipenem as selective pressure led to a duplication of this gene on the plasmid and to the restoration of a significant carbapenem-hydrolyzing phenotype.